Chinese philosophy of life, relational ethics and the COVID-19 pandemic. Issue 1 (2nd January 2021) - Rošker, Jana S.
ABSTRACT: This paper investigates the relation between different models of ethics and their impact upon crises solution strategies. Here, it is important to consider knowledge and ethical theories from different cultures. The paper describes some alternative ethical models from the perspective of the Chinese, particularly Confucian, philosophies. This perspective is meaningful because in the Sinitic areas the pandemic has been brought under control much more effectively than in other regions of the world. First, the paper introduces the Chinese philosophy of life and highlights its current relevance; then, it presents traditional Chinese models of relational and anti-essentialist concepts of the self and investigates their impact to the Confucian models of social ethics. On this basis, it illuminates some new ways of understanding interpersonal and intercultural interactions that might help us develop new strategies against current and future pandemics.